Research on Dynamic Virtualization Distributed Mobility Management Method for LEO Satellite Network - Hongtao ZHU; Qing GUO (天地一体化信息网络)
With the commercialization of 5G,the integration of satellite communication and ground 5G has become a key research direction in the industry.Low earth orbit satellite network can cover the whole world and communicate with anyone at any time and anywhere.It is an eff ective supplement and expansion of terrestrial cellular network.Especially,the deployment of low earth orbit (LEO) internet constellation such as OneWeb and Starlink accelerates the development of LEO satellite network.However,due to the high dynamic of LEO satellite and the fast change of its network topology,the network management problem caused by it has become the diff culty of LEO satellite application,and mobility management is one of the key technologies.How to build a mobility management mechanism suitable for high dynamic LEO satellite network is an urgent problem to be solved.Based on the idea of ground distributed gateway and satellite agent cluster,the dynamic virtualization distributed mobility management (DV-DMM) model was proposed,which was mainly used to solve the problems of poor scalability and single point failure of traditional mobility management.At the same time,it used satellite to build virtual gateway to solve the problem of building satellite ground station on the ground.